2017
DOI: 10.1086/694297
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell Biliverdin and Protoporphyrin Pigments in a Songbird: Are They Derived from Erythrocytes, Blood Plasma, or the Shell Gland?

Abstract: Biliverdin and protoporphyrin pigments are deposited into the eggshell when the developing egg is in the shell gland. However, the site of synthesis of eggshell pigments is still uncertain, although it may influence the possible costs and potential functions of eggshell coloration in avian species. Eggshell pigments may be derived from red blood cells or be produced in other organs and then transferred to the shell gland, or they may be synthesized de novo in the shell gland. We studied in the canary (Serinus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…In our population, female great tits that lay eggs in the beginning of the breeding season, when caterpillar food availability is scarce, and those that have smaller clutches lay darker‐spotted eggs (Hargitai et al , c), indicating that food limitation may lead to more pigmented eggshells. Moreover, some experimental and observational studies of other bird species also indicated that food limitation resulted in darker spotted eggshells (Duval et al , Hargitai et al , 2018a, Badás et al ). Therefore, it is possible that females in less favourable conditions laid darker spotted eggs, and due to energetic constraints they delayed the start of incubation, resulting in more synchronous broods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our population, female great tits that lay eggs in the beginning of the breeding season, when caterpillar food availability is scarce, and those that have smaller clutches lay darker‐spotted eggs (Hargitai et al , c), indicating that food limitation may lead to more pigmented eggshells. Moreover, some experimental and observational studies of other bird species also indicated that food limitation resulted in darker spotted eggshells (Duval et al , Hargitai et al , 2018a, Badás et al ). Therefore, it is possible that females in less favourable conditions laid darker spotted eggs, and due to energetic constraints they delayed the start of incubation, resulting in more synchronous broods.…”
Section: Discussionmentioning
confidence: 99%
“…Red‐brown eggshell maculation is generated by protoporphyrin pigment (Kennedy and Vevers , Mikšík et al , Gorchein et al ) that is most likely produced in the shell gland (Zhao et al , Wang et al , Hargitai et al ). Apart from its widespread role to camouflage the eggs (Stoddard et al , Spencer et al ), )a great number of hypotheses have been proposed in recent years for the evolution of eggshell pigmentation (Kilner , Reynolds et al , Maurer et al ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma biliverdin is mainly produced in the spleen from degrading erythrocytes, and then released into the circulation, and transferred to the liver (Murray 2003). However, several studies of poultry (Yamada 1972, Stevens et al 1974, Zhao et al 2006, Wang et al 2009, 2011, and a recent study of the canary (Hargitai et al 2017) suggest that eggshell biliverdin is most likely produced in the shell gland by the oxidation of heme, which could be produced in the cells of the shell gland. If circulating biliverdin inhibits by some negative feed-back mechanism the activity of enzymes in the synthesis pathway of eggshell biliverdin in the shell gland, it could provide a possible explanation for the effect of food/antioxidant availability and body condition on eggshell blue-green coloration.…”
Section: Blue-green Eggshell Pigmentationmentioning
confidence: 99%